ABA signaling converts stem cell fate by substantiating a tradeoff between cell polarity, growth and cell cycle progression and abiotic stress responses in the moss Physcomitrium patens - Beier, Marcel Pascal; Jinno, Chiyo; Noda, Natsumi; Nakamura, Kohei; Sugano, Sumio; Suzuki, Yutaka; Fujita, Tomomichi (Frontiers in Plant Science, 2023)
Abscisic acid (ABA)-mediated abiotic stress tolerance causes plant growth inhibition. Under such stress conditions, some mosses generate de novo stress-resistant stem cells, also called brood cells or brachycytes, that do not exist under normal conditions. However, the cell physiological basis of the growth inhibition and the stem cell formation is not well understood. Here, we show that the ABA-induced growth inhibition of the moss Physcomitrium patens apical protonemal cells (protonemal stem cells) is mediated through a shift from asymmetric to symmetric cell division. This change of the cell division mode, and consequently change of stem cell activity, is substantiated by dampening cell polarity and cell proliferative activity through the altered distribution of cytoskeletal elements, the mitotic spindle and the vacuole, which results in the production of stress-resistant stem cells. Alteration of the cell physiological data is supported by the results of RNAseq analysis indicating rapid changes in both cell polarity and cell cycle regulation, while long-term treatments with ABA for 5 to 10 days impact mainly the transcriptional and translational regulation. The regulation of cell polarity and cell cycle genes suggests growth arrest mediated by small GTPases (ROPs) and their guanine exchange factors (ROPGEFs) and by cyclin and cyclin-dependent-kinase complex, respectively. Our data suggest that a tradeoff relationship between growth ability and abiotic stress response in the moss is substantiated by ABA signaling to suppress cell polarity and asymmetric cell growth and may play a pivotal role in stem cell fate conversion to newly produced stress-resistant stem cells.